The complex relationship of gene duplication and essentiality. - Mc Lysaght, Aoife; Hokamp, Karsten (My University, 2009)
In yeast and worm, duplicate genes overlap in function so that deleting one of a pair from the genome is less likely to be lethal than deleting a singleton gene. By contrast, previous analyses showed that mouse duplicate genes were as essential as singletons. We show that the relationship between gene duplication and essentiality is complex in multicellular organisms, with developmental genes and genes that were duplicated by whole genome duplication being more essential than other duplicated genes.
PUBLISHED
Keywords: Genetics; singleton gene; Genes & Society